STRATEGI KINERJA KEUANGAN: Free Cash Flow dan Prudence dalam Meningkatkan Kualitas Laba - Fauzi, Kusmul; Sutandijo, Sutandijo; Sugiyarti, Listya (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine and provide empirical evidence regarding the influence of Financial Performance, Free Cash Flow, and Prudence on Profit Quality. The independent variables in this research are Financial Performance as measured by Return on Assets (ROA), Free Cash Flow as measured by the Free Cash Flow Index (FCF), and Prudence as measured by the Conservatism Index (CONACC). The dependent variable in this research is the Quality of Earnings as measured by the Quality of Earnings Ratio. This type of research is quantitative research using secondary data in the form of annual financial reports originating from the official website of the Indonesia Stock Exchange (BEI) and the official website of each company. Population in this research are energy sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sampling technique in this study used purposive sampling, 19 companies were obtained as research samples. The data analysis technique in this study used the multiple linear regression analysis method using the software analysis tool Eviews version 12. The research results showed that (1) Performance Finance, Free Cash Flow, and Prudence, together (simultaneously) have a significant effect on Earnings Quality. (2) Financial Performance partially has no effect on Earnings Quality (3) Partially Free Cash Flow has no effect on Earnings Quality (4) Prudence partially has a significant positive effect on Earnings Quality.